A Spiritual Theology of Synodality: Towards a Thinking Heart in Catholic Education - Glenn Morrison (Religions, 2023)
Spiritual theology inspires a life of faith towards wisdom and discernment as much as inviting a developing pastoral sense of God’s mysteries into a life of service, holiness and humility. Akin to practical theology, spiritual theology is fragmented and interconnects with all areas of theology. The article sets out to put spiritual theology into service to present Pope Francis’ ecclesial turn towards synodality within a spiritual and ethical metaphysical domain. To this end, the article also employs the philosophy of Emmanuel Levinas to help bring out the effect and contribution of spiritual theology upon synodality. The aim here is to develop Pope Francis’ hope and vision of synodality of journeying together through mission and dialogue by way of conversion and reform, hospitality, gentleness and listening. The article, in conclusion, moves forward to look at how synodal spirituality may also orient a thinking heart in Catholic Education.